First, let's simplify the expression inside the parentheses:
(3/9⋅12)^2−(2−3)^3
We can start by simplifying the first part: (3/9⋅12)^2
To simplify this, we first calculate the value inside the parentheses:
3/9⋅12 = 1/3⋅12 = 4
Now we have (4)^2, which equals 16.
Next, let's simplify the second part: (2−3)^3
2−3 = -1
Now we have (-1)^3, which equals -1.
Finally, we substitute the simplified values back into the original expression:
(3/9⋅12)^2−(2−3)^3 = 16 - (-1) = 16 + 1 = 17
Therefore, the solution is 17.
Solve the multi-step problem (3/9⋅12)^2−(2−3)^3
1 answer